(untitled) - Nguyễn, Đình Chúc (Hà Nội, 2011)
Giới thiệu lịch sử hình thành các địa danh của tỉnh Phú Yên. Các địa danh được thể hiện qua tục ngữ, ca dao.
Keywords: Names, Geographical,Folk poetry, Vietnamese,Tên, địa lý,Ca dao Việt Nam; Vietnam,Phú Yên (Vietnam : Province),Việt Nam,Tỉnh Phú Yên